ANALYSIS OF PT WASKITA KARYA TBK'S FINANCIAL STATEMENT FRAUD DUE TO RESTATEMENT AND RESTRUCTURING - Sari, Ni Kadek Dian Mayang; Sinarwati, Ni Kadek; Savitri, Ni Luh Asri (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study aims to analyze indications of financial statement fraud before and after the restatement and restructuring at PT Waskita Karya Tbk for the 2019–2024 period. This research is based on the phenomenon of financial performance pressure, financial statement restatements, and debt restructuring, which can affect the quality of a company's financial reporting. The population in this study was the Annual Financial Report of PT Waskita Karya Tbk for the 2019–2024 period. This study used a saturated sampling technique, with a total of 24 observations. The research method used was quantitative descriptive using the Dechow F-Score model. The results showed that before the restatement and restructuring, the F-Score value for the 2022 period was 1.065, indicating financial statement fraud. This was due to the company facing a high debt burden and declining financial performance. However, after the restatement and restructuring, all observation periods were in the non-manipulator category, indicating no indication of financial statement fraud based on the model testing results. This condition indicates that the financial reporting practices carried out did not lead to fraudulent acts, but rather efforts to adjust and improve the quality of financial information.